Gut microbial bile and amino acid metabolism associate with peanut oral immunotherapy failure - Mustafa Özçam; Din L. Lin; Chhedi L. Gupta; Allison Li; J. Carlos Gomez; Lisa M. Wheatley; Carolyn H. Baloh; Srinath Sanda; Stacie M. Jones; Susan V. Lynch (Nature Communications)
Abstract Peanut Oral Immunotherapy (POIT) holds promise for remission of peanut allergy, though treatment is protracted and successful in only a subset of patients. Because the gut microbiome has been linked to food allergy, we sought to identify fecal predictors of POIT efficacy and mechanistic insights into treatment response. Here, we conducted a secondary analysis of the IMPACT randomized, double-blind, placebo-controlled POIT trial (NCT01867671), using longitudinal fecal samples from 90 children, and performed 16S rRNA sequencing, shotgun metagenomics, and untargeted metabolomics. Integrated multi-omics analyses revealed a relationship between gut microbiome metabolic capacity and treatment outcomes. Five fecal bile acids present prior to treatment initiation predicted POIT efficacy (AUC 0.71). Treatment failure was associated with a specific bile acid profile, enhanced amino acid utilization, and higher copy number of the ptpA gene encoding a bacterial hydrolase that cleaves tripeptides containing proline residues – a feature of immunogenic peanut Ara h 2 proteins. In vitro, peanut-supplemented fecal cultures of children for whom POIT failed to induce remission evidenced reduced Ara h 2 concentrations. Thus, distal gut microbiome metabolism appears to contribute to POIT failure.